Success Predictor Factors In Entrepreneurship: Case Study Of Micro MSMEs Pinisi Miniature Ship Craftsmen In Mojokerto Regency - Moh. Faizin; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Abadi Institute, 2026)
This study aims to identify factors that are predictors of success in entrepreneurship in micro MSMEs miniature artisans of Pinisi ships in Mojokerto Regency. The case study approach was used by collecting data through in-depth interviews, participatory observations, and documentation of 15 miniature artisans of Pinisi ships. The analysis was carried out qualitatively by focusing on internal factors such as motivation, technical skills, business management, and external factors such as family support, marketing network, and access to capital. The results of the study show that technical skills, managerial skills, and marketing networks are the main predictors of the success of MSMEs. In addition, family support and the ability to innovate also play a significant role in maintaining business continuity. These findings provide implications for the development of training programs and policy support for local creative MSMEs.